2006
DOI: 10.1109/tip.2006.881965
|View full text |Cite
|
Sign up to set email alerts
|

Ground Target Recognition Using Rectangle Estimation

Abstract: We propose a ground target recognition method based on 3D laser radar data. The method handles general 3D scattered data. It is based on the fact that manmade objects of complex shape can be decomposed to a set of rectangles. The ground target recognition method consists of four steps; 3D size and orientation estimation, target segmentation into parts of approximately rectangular shape, identification of segments that represent the targets functional/main parts and target matching with CAD models. The core in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 24 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…This can be done by a rectangle estimator developed by Gronwall et al [22]. We tested this rectangle estimator to derive width and height of three boats (No.…”
Section: Extracting 2d and 3d Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done by a rectangle estimator developed by Gronwall et al [22]. We tested this rectangle estimator to derive width and height of three boats (No.…”
Section: Extracting 2d and 3d Informationmentioning
confidence: 99%
“…A somewhat simpler, but maybe less robust, 3D target recognition technique have been developed at FOI [22]. It was developed for ground vehicle recognition but has been used for land mine recognition as well.…”
Section: Extracting 2d and 3d Informationmentioning
confidence: 99%
“…The formula which gives the middle point of the object is as follows [15]: (3) N indicates the number of comer pixels. The Euclidean distance between pixels P and Q is calculated as follows for P=(xl,yl) and Q=(x2,y2) points [16]: In Figure 6, the distances to the point taken as reference for the determination of the middle point of the object are shown. When calculating the middle point, the entire image received from the camera is considered as an object, and the locations outside of the object are treated as empty space.…”
Section: Target Recognitionmentioning
confidence: 99%
“…Tests have shown that when there are at least 50 samples distributed over the target, its dimensions can be determined with a 10% uncertainty [4]. Usually this is enough to determine its class.…”
Section: Introductionmentioning
confidence: 99%
“…Usually this is enough to determine its class. To determine the target type, usually at least 200 well-distributed target samples are needed [3,4]. It is thus desirable to be able to increase the number of such samples by incorporating data obtained from several measurements, either with one sensor moved to different positions or with several sensors in a sensor network.…”
Section: Introductionmentioning
confidence: 99%